Interreligious harmony is as the basis of interaction between government and religion (Journal of Philosophy Culture and Political Science, 2018)
Interreligious harmony is the most important element of stability in any society. Saving interfaith and international peace can be built only on the joint relationship between the state and religious associations. In this regard Kazakhstan, where more than 100 nations and nationalities live and speak different languages, could not only manage to maintain peace on their own territory, but also contributes its strengthening and development in the international arena. Additionally, for the modern Kazakhstan it is characterized that the coexistence on equal rights of different religions, balance the relationship between which is supported by the development of the same interest of state policy to all confessions, formation a culture of tolerance in terms of parity before the law. Due to deeply considered national politics in modern Kazakhstan there are establishing new interethnic and interfaith relations, appearing the prerequisites of forming a multi-ethnic and multiconfessional community of Kazakhstan people with common goals, ideals, and values. Special importance is the reinterpretation of dialectical relationship of ethnic and religious aspects in the Kazakh culture, their appearance in the mentality, lifestyle, social memory and the process of selfidentification. In this article are available the materials about problems of interethnic and interfaith relations in Kazakhstan. In general, the main conclusions of the article complement the concepts of modern historical scholarship about problems of religious harmony. Key words: religion, the state, society, interreligious harmony, identity.